SEROPREVALENCE OF SCRUB TYPHUS AMONG FEBRILE PATIENTS – A PRELIMINARY STUDY - K.USHA; KUMAR, E.; KALAWAT, USHA; KUMAR, B. SIDDHARTHA; CHAUDHURY, A.; SAI GOPAL, DVR. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Aim: Scrub typhus is a vector borne zoonotic diseases re-emerging in India. But there are no reports from Andhra Pradesh till date due to low index of suspicion and lack of diagnostic facilities. This emphasizes the need for a study on this re-emerging Zoonosis. Methodology: A total of 280 sera samples with pyrexia of unknown origin were screened by using Weil-Felix test, rapid immunochromatographic method and ELISA. Result: Among the tested 280 febrile ill patients, 158 (56.42percent) was found to be positive by Weil-Felix test, 163 (58.21percent) was positive by ELISA and 160 (57.14percent) was positive by immunochromatographic test. Conclusion: By this study it can be inferred that awareness about vector borne zoonotic diseases is crucial. Clinical practice, epidemiological surveys and definite diagnostic tests have to be developed to study this neglected area, since this condition is very much prevalent in this part of the country. Â Keywords: Febrile illness; Spotted fever group; Typhus fever group; Scrub typhus; Weil-Felix test; Immunochromatographic test; ELISA.